The fading of fear effects due to coral degradation is modulated by community composition. (3rd September 2020) - Ferrari, Maud C. O.; McCormick, Mark I.; Fakan, Eric; Barry, Randall; Chivers, Douglas P.
Abstract: An increasing number of coral reefs throughout the world have become degraded as a result of climate change. This degradation has resulted in a significant decline in local biodiversity. Studies have shown that some fishes (non‐responders) within these altered habitats are not able to adequately access olfactory cues, specifically chemical alarm cues that are crucial in mediating predation risk. We propose that the inability to access this crucial information is a potential mechanism for increased mortality of these species under natural conditions. However, we posit that the presence of certain key species (responders that are unaffected by degradation) may buffer the handicap of non‐responders by providing an alternate source of information. To explore this hypothesis, we investigated if a high ratio of responders to non‐responders could mitigate the impact of information loss for the affected species. Using mesocosms, we manipulated the ratio of two damselfish species, Pomacentrus chrysurus (responder) and P. moluccensis (non‐responder), to determine if community composition can be predictive of information transfer about predation threats in nearby non‐responder individuals. Our results indicate that, in degraded environments, the magnitude of fear effects seen in P. moluccensis exposed to a predator was proportional to the number of P. chrysurus present and consumed by the predator in the community. This indicates that P. chrysurus became the only functional source of predation‐related information for P. moluccensis in degraded habitats. These results contrasted with those from live coral environments, where all individuals exhibited fear effects, regardless of community composition. Our study provides evidence that the presence of non‐affected species in the community provides a potential mechanism allowing increased resilience by affected species, therefore providing another example of the way biodiversity affects ecological resilience of species in changing ecosystems. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.